1999
DOI: 10.1023/a:1008901428552
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hydroxyapatite powders were made by reacting orthophosphoric acid with calcium hydroxide and dense bioactive coatings were subsequently produced by the plasma spray technique. Three types of hydroxyapatite (flame spheroidized) monolayer coatings and three types of functionally graded coatings were manufactured. It was found that average microhardness values of monolayer coatings decreased as the indentation load increased. The relationship between indentation load and indent diagonal length observed Meyer's la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It could be attributed to nano-sized constituent phases and a high elastic modulus of prepared composite coatings. Fracture toughness of coatings increases as the particle size of constituent phases decreases [32]. Fig.…”
Section: Sem and Afm Evaluations And Edx Analysismentioning
confidence: 92%
“…It could be attributed to nano-sized constituent phases and a high elastic modulus of prepared composite coatings. Fracture toughness of coatings increases as the particle size of constituent phases decreases [32]. Fig.…”
Section: Sem and Afm Evaluations And Edx Analysismentioning
confidence: 92%
“…Moreover, release of toxic metal ions from metallic implants also causes health concerns due to the allergic body response [8]. To make implants of these materials bioactive and to achieve their good bonding with living bone, various surface modification techniques such as plasma spraying [9], sprayingand-sintering [10], magnetron sputtering [11], ion beam-assisted deposition [12], and biomimetic deposition [13] have been investigated for forming a bioactive calcium phosphate or apatite layer on the metal surfaces. These bioactive ceramic coatings can also provide physical barriers to prevent or retard the release of toxic heavy metal ions from metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…Metals provide implants with the strength and toughness that are required in load-bearing parts of the human body and due to these advantages, metals will continue to play an important role as orthopaedic biomaterials in the future. To overcome the problem of bioinertness of metallic biomaterials and promote bone formation on metallic implants, various surface modification methods have been investigated to form osteoconductive calcium phosphate or glass coatings on the metals [2][3][4][5][6][7]. Among these surface modification techniques, the biomimetic deposition technique appears very attractive and promising [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on mechanical properties of biomimetically deposited apatite coatings have been rarely reported. Nevertheless, it was shown that microhardness testing and nanoindentation could be used to assess mechanical properties of plasma sprayed hydroxyapatite (HA) coatings [2,11], bioactive coatings made by the spraying-and-sintering technique [3] and bone-like apatite formed through biomimetic processes [12]. It was also demonstrated that scratch tests could be used to assess the adhesion of a bioactive glass coatings to the metal substrate [6].…”
Section: Introductionmentioning
confidence: 99%